Floristic relationships of terra firme forests in the Brazilian Amazon - Oliveira, A. A. de; Nelson, B. W. (Elsevier B.V., 2001)
Multivariate analyses of floristic composition at the genus level were performed on a set of 31 tree inventories from 12 sites in the Brazilian Amazon, one site in the Bolivian Amazon, and one in the northeast Brazilian Atlantic coastal forest. All plots are terra firme forests on clay or loam soil. Rainfall ranges from 1600 to 2600 mm/year. Floristic dissimilarity between plots was associated with three factors: (1) physiognomic type, with a distinct separation between evergreen 'dense' and the more seasonal 'open' forests; (2) geographic distance and (3) past disturbance. Among the dense forest plots those from central Amazonia are floristically intermediate between western and eastern regions, strengthening the hypothesis that central Amazonia is an area of phytogeographical confluence. Based on this work forest physiognomy and distance have been suggested to policy-makers as unbiased indicators of Aoristic dissimilarity and these proxies are now being used to define priority conservation areas for the Brazilian Amazon. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: amazon phytogeography; forest inventory; multivariate analysis; conservation planning